ANALISIS RANTAI DISTRIBUSI KOMODITAS PADI DI KABUPATEN GROBOGAN - Wiwin Widiastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
The aims of the reasearch were to identify the rice commodity distribution pattern, to identify the profit margin level of rice commodity and to analyse the government policy in suporting the distribution of rice commodity. Research location was in Grobogan Regency as the big third of rice producers in Central Java Province. The unit of analysis were paddy field farmer and the broker of rice commdity in Grobogan Regency. The research results showed that there were three patterns of rice commodity distribution,(1) farmer - merchant middleman - ricemills - merchant wholesellers - retailers - consumers; (2) farmer - merchant middleman - ricemill - retailers – consumers; and (3) farmer - ricemill - merchant wholesellers - retailers - consumers. With such existing distribution pattern, the actors of rice trade able to get their profits. The profit margin in rice distribution are merchant middleman (Rp 150/kg), rice mills (Rp 150/kg), merchant wholesellers (Rp150/kg) and retailer (Rp100/kg). Marketing innovation namely “Tani niaga”on-line base application was one of Grobogan regency government policy which supports farm commodity distribution and marketing system.